2020
DOI: 10.1080/09650792.2020.1724813
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing system thinking - a superintendent and three principals reflecting with a critical friend

Abstract: There is a growing body of action research on school improvement and development. Many of these studies have found the use of critical friendship valuable in relation to teachers' or principals' practice. Yet, little attention has been paid to critical friendship at the school district level. This study explores how a superintendent and three principals changed their understandings through interaction with a critical friend. It draws on reflective conversations, written reflections and observations of meetings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…The fact that a strong correlation between attitudes and knowledge was reported is consistent with prior research conducted on educational management. Although not specifically regarding active learning methodologies, previous studies by Berger, Reupert, and Hasking [74], Swanson and Gettinger [75], Kuyini, Desai, and Sharma [76], Henriksen and Aas [77], and Touloupis and Athanasiades [78] also indicated that principals' attitudes and knowledge are strongly related, according to these studies, in aspects such as educational inclusion or attention to diversity. As Barnett and Monda-Amaya [79], Watkins, Anthony and Beard [80], and Nadav, Benoliel, Shaked and Schechter [81] pointed out, this phenomenon may be because in the field of education, increased knowledge in a field of study usually leads to an increase in a positive attitude towards that subject.…”
Section: Discussionmentioning
confidence: 79%
“…The fact that a strong correlation between attitudes and knowledge was reported is consistent with prior research conducted on educational management. Although not specifically regarding active learning methodologies, previous studies by Berger, Reupert, and Hasking [74], Swanson and Gettinger [75], Kuyini, Desai, and Sharma [76], Henriksen and Aas [77], and Touloupis and Athanasiades [78] also indicated that principals' attitudes and knowledge are strongly related, according to these studies, in aspects such as educational inclusion or attention to diversity. As Barnett and Monda-Amaya [79], Watkins, Anthony and Beard [80], and Nadav, Benoliel, Shaked and Schechter [81] pointed out, this phenomenon may be because in the field of education, increased knowledge in a field of study usually leads to an increase in a positive attitude towards that subject.…”
Section: Discussionmentioning
confidence: 79%
“…To capture the longitudinal aspects of the study, the group meetings were repeated four times between September 2018 and June 2019. The researchers/leadership supervisors acted as critical friends, assisting throughout the questioning and providing reflection and other viewpoints (Henriksen and Aas 2020;Swaffield 2004). A critical friend can be seen as a shoulder to lean on and is like the role of a leadership coach, who can contribute to principals' learning through contributing critical questions and reflections that can lead to new leadership practices (Fluckiger, Lovett, and Dempster 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the relevance of several factors that affect organizational change management success can be explored in a different context of organizations and sectors. This is indirectly able to contribute to innovative ways of thinking, to enhance the leaders' system thinking [50].…”
Section: Discussionmentioning
confidence: 99%